2019
DOI: 10.1002/ange.201812509
|View full text |Cite
|
Sign up to set email alerts
|

Structural Snapshots of Cluster Growth from {U6} to {U38} During the Hydrolysis of UCl4

Abstract: Herein we report the assembly of large uranium(IV) clusters with novel nuclearities and/or shapes from the controlled hydrolysis of UCl4 in organic solution and in the presence of the benzoate ligands. {U6}, {U13}, {U16}, {U24}, {U38} oxo and oxo/hydroxo clusters were isolated and crystallographically characterized. These structural snapshots indicate that larger clusters are slowly built from the condensation of octahedral {U6} building blocks. The uranium/benzoate ligand ratio, the reaction temperature and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…In one study, two thiolate capped Au 28 clusters exhibited ligand-induced reversible isomerization, which resulted in different efficacies in the catalytic oxidation of CO over a CeO 2 support . In addition to thiol groups, carboxylate-based capping groups can stabilize metallic clusters. Recent work by Chatelain et al isolated a series of U 6 , U 10 , U 13 , U 16 , U 24 , and U 38 -oxo clusters, which suggested that the thermodynamically assisted condensation of isolated U 24 and U 6 clusters can access a large nuclearity U 38 motif …”
Section: Introductionmentioning
confidence: 99%
“…In one study, two thiolate capped Au 28 clusters exhibited ligand-induced reversible isomerization, which resulted in different efficacies in the catalytic oxidation of CO over a CeO 2 support . In addition to thiol groups, carboxylate-based capping groups can stabilize metallic clusters. Recent work by Chatelain et al isolated a series of U 6 , U 10 , U 13 , U 16 , U 24 , and U 38 -oxo clusters, which suggested that the thermodynamically assisted condensation of isolated U 24 and U 6 clusters can access a large nuclearity U 38 motif …”
Section: Introductionmentioning
confidence: 99%
“…On the basis of large isolatable clusters including U 38 and Np 38 (in addition to numerous examples of hexamers, i.e., refs and ), the polymerization of U IV and Np IV appear to be more similar to Pu IV than Th IV . Unlike Pu 38 , Np 38 and U 38 isolation required organic media that slow olation–oxolation reactions . In addition, neither the Np IV 2 nor U IV 2 dimer has been isolated, from either water or organic media.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike Pu 38 , Np 38 and U 38 isolation required organic media that slow olation−oxolation reactions. 36 In addition, neither the Np IV 2 nor U IV 2 dimer has been isolated, from either water or organic media. In 1973, however, the dihydroxide-bridged U 2 dimer was proposed in X-ray scattering analysis of uranium(IV) perchlorate solutions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is best evidenced in the number of ligand-decorated building units, ranging from mononuclear species to nanosized clusters . Despite the identification of a growing number of U­(IV) structural units, the effects of ligand complexation on actinide speciation remain unclear; speciation is notably further complicated by solution conditions, which are likewise known to have a sizable impact on phase formation. ,, A survey of the literature shows that ligands broadly play one of three roles: (1) competing with and/or thwarting hydrolysis and condensation, (2) directing and/or modulating the formation of larger polynuclear clusters, and (3) enabling the isolation of unique structural units that are otherwise absent from descriptions of actinide structural chemistry. Moreover, previous work has indicated that there are distinct differences between coordinating ligands (i.e., carboxylates) and noncoordinating organic species, the latter for which supramolecular interactions such as π–π stacking and hydrogen bonding may have a notable impact on speciation. , …”
Section: Introductionmentioning
confidence: 99%
“…The goals of this work are to further examine the effects of hydrolysis and condensation, ligand complexation, and solution conditions on actinide phase formation through a systematic study of U­(IV) complexation by aliphatic dicarboxylates. To date, most studies have focused on either small, monanionic ligand sets (i.e., formate, acetate, and simple amino acids , ) or those with rigid, aromatic backbones (i.e, benzoates, , pyridinedicarboxylates, terephthalates, , and furoates). Moving away from these monoanionic and/or rigid, aromatic linkers, the coordination of aliphatic dicarboxylates with U­(IV) was examined under room temperature conditions.…”
Section: Introductionmentioning
confidence: 99%